Ability to Interpret Graphs in Reaction Rate Material Based on Mathematical Understanding and Learning Style of Class XI High School Students - Rezki*, Maulidia; Hasan, Muhammad; Evendi, Evendi; Akbar, Said Ali; Zaura, Bintang; Khwaengmek, Wipavadee (Universitas Syiah Kuala, 2024)
One aspect of process science skills that learners need to have is the ability to interpret. The ability to interpret graphs in students is currently considered difficult and still belongs to the very low category. This study aims to analyze the relationship between mathematical understanding and the learning styles of students in terms of their ability to interpret graphs. This type of research is descriptive-quantitative. The research sample consisted of class XI students at SMA Negeri 4 Takengon, which amounted to 67 students. The research data was collected using learning style-type questionnaires, multiple-choice questions on linear program material, and reaction rate material. The ability to interpret the graphs of students at SMA Negeri 4 Takengon is on the